Bacterial exopolysaccharides: biosynthesis pathways and engineering strategies - Schmid, Jochen; Sieber, Volker; Rehm, Bernd (Frontiers in Microbiology, 2015)
Bacteria produce a wide range of exopolysaccharides (EPS) which are synthesized via different biosynthesis pathways. The genes responsible for synthesis are often clustered within the genome of the respective production organism. A better understanding of the fundamental processes involved in exopolysaccharide biosynthesis and the regulation of these processes is critical toward genetic, metabolic and protein-engineering approaches to produce tailor-made polymers. These designer polymers will exhibit superior material properties targeting medical and industrial applications. Exploiting the natural design space for production of a variety of biopolymer will open up a range of new applications. Here, we summarize the key aspects of microbial exopolysaccharide biosynthesis and highlight the latest engineering approaches towards the production of tailor-made variants with the potential to be used as valuable renewable and high-performance products for medical and industrial applications.